2019
DOI: 10.3389/fimmu.2019.02601
|View full text |Cite
|
Sign up to set email alerts
|

Morphine Withdrawal Enhances HIV Infection of Macrophages

Abstract: Opioid withdrawal recurs at high rates in opioid use disorder and compromises the immune system. In general, there are two types of opioid withdrawal: abrupt withdrawal (AW) and precipitated withdrawal (PW). In this study, we examined the effect of morphine AW or morphine PW on HIV infection of human blood monocyte-derived macrophages. We observed that both morphine AW and PW enhanced the susceptibility of macrophages to HIV infection. In addition, both AW and PW activated HIV replication in the latently infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…There are several factors that may be responsible for the morphine-mediated modulation of CNS SIV reservoirs. It has been reported that morphine upregulates the expression of CCR5 coreceptors in macrophages, which, in turn, could increase the viral permissiveness of these cells ( 21 , 57 , 73 ). Morphine is known to also lower the CNS penetration of several antiretrovirals, which could result in ongoing viral replication in the CNS and be responsible for the larger reservoir ( 74 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are several factors that may be responsible for the morphine-mediated modulation of CNS SIV reservoirs. It has been reported that morphine upregulates the expression of CCR5 coreceptors in macrophages, which, in turn, could increase the viral permissiveness of these cells ( 21 , 57 , 73 ). Morphine is known to also lower the CNS penetration of several antiretrovirals, which could result in ongoing viral replication in the CNS and be responsible for the larger reservoir ( 74 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are several factors that may be responsible for the morphine-mediated modulation of CNS SIV reservoirs. It has been reported that morphine upregulates the expression of CCR5 coreceptor in macrophages, which, in turn, could increase the viral permissiveness of these cells [21, 55, 69]. Morphine is known to also lower the CNS penetration of several antiretrovirals, which could result in ongoing viral replication in the CNS and responsible for larger reservoir [70].…”
Section: Discussionmentioning
confidence: 99%
“…The increasing reliance on MMT to control the HIV epidemic in IDUs calls for urgent clarification of the remaining uncertainties regarding methadone and immune function. Previous research indicated that illicit drugs (methamphetamine, morphine, and heroin), even alcohol, influenced HIV entry, activated the transcription of HIV LTR, and disordered innate immunity, thereby promoting HIV replication in human immune cells ( 44 51 ). However, not much is known about whether methadone can enhance virus infection like other drugs by regulating immune system in macrophages, one of the primary targets and reservoir of the HIV.…”
Section: Discussionmentioning
confidence: 99%